Compensation for birth related injuries in Malaysia : a need for legal reform and a suitable model for a no-fault system - Khadijah Mohd Najid (Ahmad Ibrahim Kulliyah of Laws, International Islamic University Malaysia, 2019)
As the prevailing compensatory mechanism for victims of birth-related injuries in Malaysia, the tort system has been subjected to various concerns as to its adequacy and efficiency. It has been claimed that the tort system's emphasis on individual fault fails to appreciate the complex nature of birth-related injuries, resulting in unjust and undesirable implications for the affected parties. The tort system has also been criticised as not being able to deter unsafe practices. The focus on fault breeds mistrust between healthcare providers and their patients, leading to unrestrained escalation of obstetric cost, which eventually tend to discourage the availability of obstetric services in Malaysia. Faced with similar concerns, certain jurisdictions around the globe have moved towards adopting a limited no-fault compensation specifically for birth-related injuries to complement the flaws in the existing system. The abandonment of fault in the no-fault system has been able to provide fairer, easier and wider access to compensation at an affordable cost while nurturing a collaborative relationship between the relevant parties. This research aims to investigate the practical weaknesses of the tort system in compensating victims of birth-related injuries in Malaysia, and conduct a comparative study on the workings of the no-fault compensation systems in Virginia, Florida and Japan that has been established specifically for birth-related injuries. The viability of adopting a no-fault compensation system for birth-related injuries suitable for the Malaysian local climate will be further examined. Consequently, the research will propose a suitable no-fault compensation model that has been tailored to meet the Malaysian needs, which has removed all practical weaknesses and injustices that has perpetuated in the present tort system. The proposed model will afford wider access to compensation, better deterrence of poor practice and eventually constitute a holistic move towards the improvement of the obstetrical service in Malaysia. Efforts towards embracing this holistic reform should be undertaken before the quality and availability of obstetric services in Malaysia are severely affected which will be detrimental to the society at large. With the increasing global emphasis on sustaining patient safety initiatives in the healthcare system, a change in the compensatory system for birth-related injuries in Malaysia would thus be seen to be opportune and timely.